Prevalences of ECG findings in large population based samples of men and women. Issue 6 (1st December 2000) - De Bacquer, D; De Backer, G; Kornitzer, M
Abstract : OBJECTIVE: To obtain accurate estimates of the prevalence of ECG abnormalities in the general population and to describe them in relation to age, sex, and some lifestyle related factors. DESIGN: The results were obtained from the records of 47 358 men and women participating in four large Belgian epidemiological studies during the past 30 years. All tracings were read and coded by two trained cardiologists on the basis of Minnesota code criteria. RESULTS: Prevalences of coronary heart disease and abnormal ECG findings rose exponentially with age in both sexes, with the exception of atrioventricular block and the Wolff-Parkinson-White (WPW) syndrome. Major ECG findings were observed in 6.0% of all men and 4.3% of women, resulting in a significant adjusted sex ratio of 1.66 (95% confidence interval 1.46 to 1.88). The prevalence of minor ECG changes was slightly higher among men (10.4% v 9.5% in women). The occurrence of ischaemia-like findings on the ECG was comparable between men and women (9.0% v 9.8%). Independent of age, smoking, obesity, diabetes, employment status, positive history of angina or infarction, and region, there were significantly higher prevalences of Q/QS patterns, left ventricular hypertrophy, left axis deviation, arrhythmias, and atrial fibrillation or flutter in men than in women. Right bundle branch block and WPW syndrome both occurred 3.5 times more often in men, while the prevalence of left bundle branch block was comparable between the sexes. CONCLUSIONS: The large sample size allowed a precise description of the most important ECG abnormalities. These are not rare in the adult population and most are strongly age related. Sex differences occur with some, but not all, abnormalities. The less common ECG abnormalities were more often observed among men.